Ammonia Oxidation and Nitrite Reduction in the Verrucomicrobial Methanotroph Methylacidiphilum fumariolicum SolV - Mohammadi, Sepehr S.; Pol, Arjan; van Alen, Theo; Jetten, Mike S. M.; Op den Camp, Huub J. M. (Frontiers in Microbiology, 2017)
The Solfatara volcano near Naples (Italy), the origin of the recently discovered verrucomicrobial methanotroph Methylacidiphilum fumariolicum SolV was shown to contain ammonium (NH4+) at concentrations ranging from 1 - 28 mM. Ammonia (NH3) can be converted to toxic hydroxylamine (NH2OH) by the particulate methane monooxygenase (pMMO), the first enzyme of the methane (CH4) oxidation pathway. Methanotrophs rapidly detoxify the intermediate NH2OH. Here, we show that strain SolV performs ammonium oxidation to nitrite at a rate of 48.2 nmol NO2-.h-1.mg DW-1 under O2 limitation in a continuous culture grown on hydrogen (H2) as an electron donor. In addition, strain SolV carries out nitrite reduction at a rate of 74.4 nmol NO2 .h 1.mg DW-1 under anoxic condition at pH 5 - 6. This range of pH was selected to minimize the chemical conversion of nitrite (NO2-) potentially occurring at more acidic pH values. Furthermore, at pH 6, we showed that the affinity constants (Ks) of the cells for NH3 vary from 5 to 270 µM in the batch incubations with 0.5 to 8 % (v/v) CH4, respectively. Detailed kinetic analysis showed competitive substrate inhibition between CH4 and NH3. Using transcriptome analysis, we showed up-regulation of the gene encoding hydroxylamine dehydrogenase (haoA) cells grown on H2/NH4+ compared to the cells grown on CH4/NO3- which do not have to cope with reactive N-compounds. The denitrifying genes nirk and norC showed high expression in H2/NH4+ and CH4/NO3- grown cells compared to cells growing at µmax (with no limitation) while the norB gene showed downregulation in CH4/NO3- grown cells. These cells showed a strong upregulation of the genes in nitrate/nitrite assimilation. Our results demonstrate that strain SolV can perform ammonium oxidation producing nitrite. At high concentrations of ammonium this may results in toxic effects. However, at low oxygen concentrations strain SolV is able to reduce nitrite to N2O to cope with this toxicity.